Experimental Demonstration of Colligative Properties of Solution on Material Phase Transition to Students with Intellectual Disabilities - Maryanti, Rina; Hufad, Achmad; Sunardi,; Nandiyanto, Asep Bayu Dani (International Journal of Psychosocial Rehabilitation, 2020)
This study demonstrated strategies in teaching colligative properties of solution to students with intellectual disabilities. This study used a single-subject design. Teaching process was done by combining conventional method and experimental demonstration. The conventional method was done in the first session (30 minutes) of teaching in the class. After the conventional method, the experimental demonstration was done in the next 2 sessions. The experimental demonstration was carried out by doing and observing melting and freezing of solution. We compared effect of additional of salt and sugar into water on phase transition of mixed solution (from ice to liquid and vice versa). The results showed that students’ knowledge increased. Learning material could be understood by 75% of students. Students with intellectual disabilities found it difficult to understand a complex and abstract information because they had of problems in making communication and memorizing. The experimental demonstration with interesting concrete media helped the students to understand the subject matter. In addition, to improve students’ enthusiasm, we used dye in the solution when doing the experimental demonstration.